Expression analysis of PTEN and CDKN1C/p57kip2 in cancerous tissues from Iranian patients with gastric cancer - Sohrabi, Sareh; Effatpanah, Hossein; Shabab, Nooshin; Saidijam, Massoud (European Journal of Oncology and Environmental Health, 2017)
Background: Since gastric cancer (GC) is the third prevalence cause of cancer-related death, early diagnosis can improve survival rate. Some studies indicated that loss of tumor suppressor gene (TSG) is a key event in gastric carcinoma. Based on epigenetic alteration each population is valuable to evaluate. So this study investigated the expression rate of phosphatase and tensin homolog (PTEN) and a cyclin-dependent kinase inhibitor of G1 cyclin complexes (CDKN1C) in a population in Iran. Methods: 64 gastric samples (32 tumoral gastric tissues and 32 healthy adjacent tissues) were collected from patients referred to Imam Khomeini Hospital Cancer Institute during 2008-2011. Total RNA was extracted, cDNA was synthesized, and then expression level of PTEN and CDKN1C was detected by Real time-PCR. Results: Our results displayed PTEN and CDKN1C expression significantly decreased in cancerous tissues compared to healthy adjacent tissues (P